Preparation of CdS@C Photocatalyst Using Phytoaccumulation Cd Recycled From Contaminated Wastewater - Li, Jia-Xin; Zhang, Rou-Lan; Pan, Zi-Jian; Liao, Yan; Xiong, Chao-Bin; Chen, Ming-Li; Huang, Rong; Pan, Xiao-Hong; Chen, Zhi (Frontiers in Chemistry, 2021)
Cadmium is one of the most toxic heavy metal contaminants in soils and water bodies, and poses a serious threat to ecosystems and humans. However, cadmium is also an important resource widely used in many industries. The recovery of cadmium in the form of high-value products is considered as an ideal disposal strategy for Cd contaminated environments. In this work, Pistia stratiotes was used to recycle cadmium from wastewaters through phytoaccumulation, and then transformed into carbon-supported cadmium sulfide photocatalyst (CdS@C) through carbonization and hydrothermal reaction. The CdS@C photocatalyst contained a mixture of cubic and hexagonal CdS with lowe band gap energy (2.14 eV) and high electron−hole separation efficiency, sugggesting an excellent photoresponse ability and photocatalytic efficiency. The impressive stability and photocatalytic performance of CdS@C were demonstrated in efficient photodegradation of organic pollutants. •OH and O2•- were confirmed as the major active species for organic pollutants degradation during CdS@C photocatalysis. This work provides new insights into addressing Cd contaminated water bodies and upcycling in the form of photocatalyst.